A defense of objectivism about evidential support. Issue 5 (December 2015) - Hedden, Brian
Abstract : Objectivism about evidential support is the thesis that facts about the degree to which a body of evidence supports a hypothesis are objective rather than depending on subjective factors like one's own language or epistemic values. Objectivism about evidential support is key to defending a synchronic, time-slice-centric conception of epistemic rationality, on which what you ought to believe at a time depends only on what evidence you have at that time, and not on how you were at previous times. Here, I defend a version of objectivism about evidential support on which facts about evidential support are grounded in facts about explanatoriness.